2022
DOI: 10.1111/hepr.13753
|View full text |Cite
|
Sign up to set email alerts
|

Serum matrix metalloproteinase‐7 in biliary atresia: A Japanese multicenter study

Abstract: Background Biliary atresia (BA) is among the commonest indications for liver transplantation (LT) in children. We examined whether serum matrix metalloproteinase‐7 (MMP‐7) is useful for diagnosis of BA in Japanese infants, and whether serum MMP‐7 concentrations before and after Kasai portoenterostomy (KP) predicted LT within a year. Methods Subjects under 6 months old at eight pediatric centers in Japan were enrolled retrospectively, including patients with cholestasis and normal controls (NC) without liver di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 23 publications
(60 reference statements)
1
23
1
Order By: Relevance
“…The results also showed that the serum level of MMP-7 above 1.43 ng / ml was a predictor of biliary atresia in neonates with cholestasis (diagnostic accuracy, 88%) [ 3 ]. Recently, a retrospective study in Japan of individuals under 6 months of age showed that serum concentrations of MMP-7 were higher in BA at diagnosis (median, 89.1 ng / ml) than in non-BA (11.0) or healthy neonates (10.3) were significantly higher [ 19 ]. In addition, the area under the ROC curve for MMP-7 in BA versus non-BA subjects was 0.99 (95% confidence interval, 0.96–1.00).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results also showed that the serum level of MMP-7 above 1.43 ng / ml was a predictor of biliary atresia in neonates with cholestasis (diagnostic accuracy, 88%) [ 3 ]. Recently, a retrospective study in Japan of individuals under 6 months of age showed that serum concentrations of MMP-7 were higher in BA at diagnosis (median, 89.1 ng / ml) than in non-BA (11.0) or healthy neonates (10.3) were significantly higher [ 19 ]. In addition, the area under the ROC curve for MMP-7 in BA versus non-BA subjects was 0.99 (95% confidence interval, 0.96–1.00).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the area under the ROC curve for MMP-7 in BA versus non-BA subjects was 0.99 (95% confidence interval, 0.96–1.00). However, the sensitivity and specificity at the optimal cut-off of 18.6 ng / ml for MMP-7 serum in the diagnosis of BA were 100 and 90%, respectively [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies reported the high concentration of MMP-7, significant variation in VCAM-1, HLA-DRA and CD74 as a biomarker for the diagnosis of BA. [15][16][17] Tsuda et al suggested using 99m Tc-PMT scintigraphy as a diagnostic method of BA to differentiate BA and non-BA patients. Achieving high diagnostic accuracy the authors revealed the 99m Tc-PMT scintigraphy can produce better results compared to conventional methods.…”
Section: Discussionmentioning
confidence: 99%
“…12 Studies reported the high concentration of MMP-7 among BA patients and perhaps serves as a diagnostic parameter. 15,16 BA could be due to immune-related genes (IRGs) and can serve as a biomarker. 17 Li et al conducted a study in which they studied the role of IRGs in the occurrence of BA.…”
Section: Diagnostic Methodsmentioning
confidence: 99%
“…A multicenter study conducted by Sakaguchi et al suggested that serum MMP-7 was a useful marker for the diagnosis of BA in Japanese infants. The optimal cut-off value was 18.6 ng/ml, and the sensitivity and specificity were 100 and 90%, respectively; however, serum MMP-7 could not predict liver transplantation (LT) within a year ( 12 ). Zhao et al ( 13 ) showed that GCDCA/CDCA can be used to assess the risk of BA in infants with cholestasis.…”
Section: Discussionmentioning
confidence: 99%